2009
DOI: 10.3748/wjg.15.2309
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of early gastric cancer with duodenal invasion

Abstract: The incidence of early gastric cancer (EGC) with duodenal invasion is extremely low, although advanced gastric cancer that arises in the antrum occasionally invades the duodenum. We investigated the clinicopathological features of EGC with duodenal invasion and provided strategies for clinical management. A Medline search was performed using the keyword "early gastric cancer" and "duodenal invasion". Additional articles were obtained from references within the papers identified by the Medline search. We reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…20 In addition, we have previously reported that the superficial spreading type of EGC adjacent to the pyloric ring correlates positively with a more extensive duodenal invasion. 21 Furthermore, Kunisaki et al reported that the number of metastatic lymph nodes was greater in the superficial spreading type of EGC than in the common tumor type. 10 Recurrence of EGC was shown to be significantly higher in the patient group with submucosal, node-positive, and undifferentiated tumors.…”
Section: Discussionmentioning
confidence: 98%
“…20 In addition, we have previously reported that the superficial spreading type of EGC adjacent to the pyloric ring correlates positively with a more extensive duodenal invasion. 21 Furthermore, Kunisaki et al reported that the number of metastatic lymph nodes was greater in the superficial spreading type of EGC than in the common tumor type. 10 Recurrence of EGC was shown to be significantly higher in the patient group with submucosal, node-positive, and undifferentiated tumors.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the fact that the number of gastric cancer encounters with a difficult ultra-low DS is relatively low, upper gastrointestinal surgeons will still encounter this surgical challenge. 5 Therefore, in such circumstances familiarity with alternative surgical methods such as Nissen closure, end or side tube-duodenostomy and Roux-en-Y end-to-end duodenojejunal anastomosis can provide the ability to successfully overcome the challenging surgical obstacle of the “difficult” DS. 6 While effective however, all these techniques have certain drawbacks and limitations when indented to be applied to a given surgical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer with duodenal invasion has been reported with an incidence of 15–40% [6]. Kakeji et al analyzed 95 patients with duodenal invasion by gastric cancer and found that tumor spread into the duodenum was limited to within 2 cm in 76% of the patients and to within 3 cm in 81% of the patients.…”
Section: Discussionmentioning
confidence: 99%